Extracellular traps and the role in thrombosis - Han, Tonglei; Tang, Hanfei; Lin, Changpo; Shen, Yang; Yan, Dong; Tang, Xiao; Guo, Daqiao (Frontiers in Cardiovascular Medicine, 2022)
Thrombotic complications pose serious health risks worldwide. A significant change in our understanding of the pathophysiology of thrombosis has occurred since the discovery of extracellular traps (ETs) and their prothrombotic properties. As a result of immune cells decondensing chromatin into extracellular fibers, ETs promote thrombus formation by acting as a scaffold that activates platelets and coagulates them. The involvement of ETs in thrombosis has been reported in various thrombotic conditions including deep vein thrombosis (DVT), pulmonary emboli, acute myocardial infarction, aucte ischemic stroke, and abdominal aortic aneurysms. This review summarizes the existing evidence of ETs in human and animal model thrombi. The authors described studies showing the existence of ETs in venous or arterial thrombi. In addition, we studied potential novel therapeutic opportunities related to the resolution or prevention of thrombosis by targeting ETs.